How much can we trust maternal ratings of early child development in disadvantaged samples? - Malte Sandner; Tanja Jungmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
An increasing number of panel studies use short screening questionnaires to assess infant development. Although some research examines the validity of screening questionnaires for middleclass families, knowledge about their accuracy in disadvantaged households is scarce. This paper validates a short screening questionnaire included in the German Socio-Economic Panel (SOEP) with the Bayley Scales for Infant Development (BSID) as an external criterion with a disadvantaged population. The results reveal significant correlations between the screening questionnaire ratings and the BSID scores for disadvantaged mothers. However, the concordance of maternal ratings and test results decreased in mothers with multiple risk burdens.
Keywords: J13; C42; C91; 330; Child Development; Validation of Survey Measures